IMPLEMENTASI MODUL KB PASCA SALIN TERHADAP PENGETAHUAN DAN SIKAP IBU BERSALIN - Ainal Mardiah, Devi Sulastri (Universitas Fort de Kock Bukittinggi, 2022)
One of the factors that can affect maternal mortality is pregnancy and childbirth and the child she is carrying, therefore efforts are needed in planning pregnancy and childbirth, including for women giving birth to use postpartum family planning. The Pegang Baru Community Health Center is a health center with a relatively small number of post-partum family planning participants, namely only 2 people in 2019 – 2020. This study aims to implement the post-partum family planning module on the knowledge and attitudes of maternity mothers in the work area of the Pegang Baru Community Health Center, Pasaman Regency. The design of this research was quasi-experimental with the One Group Pretest-Posttest Design approach. The population in this study were all third trimester pregnant women in the work area of the Pegang Baru Community Health Center in November, as many as 10 people. Sampling using purposive sampling technique with a sample size of 10 pregnant women. Data collection in this study used a knowledge and attitude questionnaire. Data analysis includes univariate analysis and bivariate analysis using paired t-test. The results showed that the average knowledge of the respondents before the intervention was 11.8 and after the intervention was 15.1. While the average attitude before the intervention was 32.8 and after the intervention was 39.5. There was a difference in the average knowledge of respondents before and after the intervention with an average difference of 3.3 and p = 0.000. There was a difference in the average attitude of respondents before and after the intervention with an average difference of 6.7 and p value = 0.000. Where there was an increase after the intervention. It can be concluded that the implementation of the post-partum family planning module has a significant effect on the knowledge and attitudes of third trimester pregnant women about post-partum family planning. It is hoped that the Pegang Baru Community Health Center will be able to use the module as a media for post-partum family planning education for pregnant women. Keywords : Module, Post-partum Family Planning, Knowledge, Attitude